2020
DOI: 10.1002/esp.4882
|View full text |Cite
|
Sign up to set email alerts
|

Use of terrestrial photosieving and airborne topographic LiDAR to assess bed grain size in large rivers: a study on the Rhine River

Abstract: Most grain size monitoring is still being conducted by manual sampling in the field, which is time consuming and has low spatial representation. Due to new remote sensing methods, some limitations have been partly overcome, but methodological progress is still needed for large rivers as well as in underwater conditions. In this paper, we tested the reliability of two methods along the Old Rhine River (France/Germany) to estimate the grain size distribution (GSD) in above-water conditions: (i) a low-cost terres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 64 publications
1
25
0
2
Order By: Relevance
“…Wavelet analysis and autocorrelation have also been demonstrated as being capable of extracting grain-size information from imagery (Rubin, 2004;Buscombe, 2008;Buscombe and Masselink, 2009;Buscombe et al, 2010). Chardon et al (2019) tested the automatic Buscombe procedure on underwater images and showed solar lighting conditions and particle petrography influence significantly the GSD. They proposed procedures to correct these effects and determine the optimal sampling area to accurately estimate the different grain size percentiles when using such a technique, which is still the only accurate approach to characterize grain size underwater.…”
Section: Detection and Characterization Of Fluvial Forms And Their Atmentioning
confidence: 99%
See 2 more Smart Citations
“…Wavelet analysis and autocorrelation have also been demonstrated as being capable of extracting grain-size information from imagery (Rubin, 2004;Buscombe, 2008;Buscombe and Masselink, 2009;Buscombe et al, 2010). Chardon et al (2019) tested the automatic Buscombe procedure on underwater images and showed solar lighting conditions and particle petrography influence significantly the GSD. They proposed procedures to correct these effects and determine the optimal sampling area to accurately estimate the different grain size percentiles when using such a technique, which is still the only accurate approach to characterize grain size underwater.…”
Section: Detection and Characterization Of Fluvial Forms And Their Atmentioning
confidence: 99%
“…With the advent of hyperspatial RS solutions at larger scales, grain-scale information can now cover entire river reaches of several kilometres in length. The airborne LiDAR topographic survey can also accurately generate grain-size maps when the point density is high (38-49 points m À2 , mean distance between points of 0.08-0.09 m) and the laser spot size fairly low (0.12 m at NADIR; see Chardon et al, 2019), comparative to observed grain sizes, allowing areas much larger than with drones to be covered.…”
Section: Detection and Characterization Of Fluvial Forms And Their Atmentioning
confidence: 99%
See 1 more Smart Citation
“…Other recent efforts use lidar or structure‐from‐motion point clouds and/or imagery to measure grains (e.g., Carbonneau et al., 2018; Chardon et al., 2020; Lang et al., 2020; Woodget et al., 2018). These are useful, but they still rely on texture‐based rather than segmentation‐based approaches to grain sizing (Purinton & Bookhagen, 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…Other recent efforts use lidar or structure-from-motion point clouds and/or imagery to measure grains (e.g.,Carbonneau et al, 2018;Chardon et al, 2020;Lang et al, 2020;Woodget et al, 2018). These are useful,…”
mentioning
confidence: 99%